DOP46 Metabolic adaptation to ER stress licences STING signalling in intestinal epithelial cells. (21st January 2022) - Wottawa, F; Becker, B; Bakr, M; Kugler, J; Mayr, L; Paludan, S; Blumberg, R; Kaser, A; Adolph, T; Schreiber, S; Meiser, J; Rosenstiel, P; et al.
Abstract: Background: Chronic endoplasmic reticulum stress (ER) in the intestinal epithelium is a pathophysiological hallmark of IBD. cGAS/STING is an innate immune pathway involved in the detection of double stranded DNA fragments leading to the subsequent induction of type I IFN responses. We here tested the hypothesis that chronic ER stress impairs cGAS/STING signalling in the intestinal epithelium. Methods: Mice with a conditional intestinal epithelial deletion of Xbp1 (Xbp1 ΔIEC, Xbp1 fl/fl ) were used to assess intestinal epithelial STING expression in-vivo. Small intestinal organoids ( Xbp1 ΔIEC, Xbp1 fl/fl ) and cell lines (Mode K, iCtrl and iXbp1 ) were used to assess cGAS/STING signalling in-vitro using STING agonist (dsDNA, DMXAA). Murine cytomegalovirus (mCMV) infection assays were performed in iCtrl and iXbp1cells and Xbp1 ΔIEC, Xbp1 fl/fl mice to functionally link impaired cGAS/STING to pathogen response. LC-MS profiling was performed in iCtrl and iXbp1cells to identify underlying metabolic programs affecting cGAS/STING responses in ER-stressed cells. IBD biopsy samples (cross-sectional, longitudinal therapy response cohort) were used to validate key molecular phenotypes in human IBD. Results: Compared to Xbp1 fl/fl mice, Xbp1 ΔIEC show completely abrogated STING expression in the basal crypt compartment of the small intestinal epithelium. In line with that iXbp1 ModeK cells displayed impaired pathway activation (TBK1) and interferon inducible gene expression ( Cxcl10 ) in response to cGAS/STING stimulation and towards mCMV infection, leading to increased viral replication compared to iCtrl cells. In-vivo mCMV infection led to augmented small intestinal histopathological disease activity in Xbp1 ΔIEC, but not Xbp1 fl/fl mice. Using LC-MS, we show that ER-stress induces a metabolic adaptation towards increased serin/glycin metabolism, which is used to counterbalance reactive oxygen species (ROS) via glutathione (GSH) synthesis. Pharmacological interception of key pathways of GSH synthesis of deprivation of serin/glycin phenocopies ER-stress in abrogating STING signalling in IECs. Lastly, we show that key aspects of metabolic adaptation to ER-stress are present in intestinal biopsies of IBD patients. Conclusion: Our data describe a novel mechanism of metabolic adaptation to compensate ER-stress and maintain intestinal epithelial cGAS/STING signalling. We therefore put forward a model of ER-stress driven immunodeficiency via cGAS/STING signalling which renders the intestinal mucosa susceptible towards CMV infection in the context of IBD.